PENGARUH PEMUPUKAN FOSFOR DAN KALSIUM TERHADAP SERAPAN HARA DAN PRODUKTIVITAS DUA GENOTIPE KEDELAI PADA BUDIDAYA JENUH AIR - Toyip Toyip (Agroland: Jurnal Ilmu-ilmu Pertanian, 2013)
The objective of this research was to study the effect of phosphorus (P) and calcium (Ca) fertilizers on productivity and nutrient uptake of two soybean genotypes under saturated soil culture.          The experimental design was a Split Split plot with three factors i.e. P fertilizer, Ca fertilizer and genotype planted under saturated soil culture. Saturated soil culture with P fertilizer (72 kg P2O5 ha-1) and lime (1 ton ha-1) increased the number of pods and grain weight plot-1. Tanggamus variety had higher number of pods and grain weight per plot than Anjasmoro variety. Interaction of phosphorus fertilizer 72 kg P2O5 ha-1 with lime 1 ton ha-1 increased grain weight plot-1. Largest direct effect on increasing grain weight is plant height and the number of branches. The application of P fertilizer (72 kg P2O5 ha-1) and liming (1 ton ha-1) also gave highest uptake of P and Ca.  Saturated soil culture technology can be applied to increase soybean nutrient uptake and productivity. Key Words : Productivity, Soybean, saturated soil culture.